Sinergi Kuliner dan Pariwisata: Pelatihan Pengolahan Hasil Laut di Desa Bugbug, Karangasem - sunada, I Nyoman; Atmaja, I Made Purwa Dana; Kristiana, Nina Indra; Rumadana, I Made; Pujawan, Anak Agung Ketut Alit; Martadjaya, I Gusti Made Iwan Dusanta; Sudiarta, Ngakan Putu; K.P Dalem, Anak Agung Gd Putra; Hendrayana, I Made; Trisdayanti, Ni Putu Eka; Kartini, Luh Putu; Winata, Gede Adi Sistha; Hardina (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This study aimed to enhance the skills and knowledge of the local community in Desa Bugbug, Karangasem, in processing seafood to develop the culinary industry and boost tourism. A combination of qualitative and quantitative approaches was employed, focusing on practical training and continuous mentoring. Data were collected using questionnaires distributed to participants before and after the training sessions, complemented by short interviews. The data were analysed to identify changes in competency levels, focusing on five key variables: culinary skills and knowledge, hygiene and sanitation awareness, professionalism and collaboration, sustainable culinary industry development, and training quality and effectiveness. The results indicated significant improvements in participants' culinary skills and knowledge, particularly in seafood processing, and heightened awareness of hygiene and sanitation practices. However, challenges in professional collaboration and the sustainable development of the culinary industry were identified. The training had a positive impact, increasing local culinary skills and knowledge, enhancing menu diversity, and supporting the preservation of traditional culinary practices. Continuous mentoring from academic institutions is crucial to further develop these competencies and ensure long-term benefits. Future research should explore integrating digital technology into training programs and evaluate the long-term economic impact on local tourism. Overcoming logistical challenges and resistance to new techniques are essential for sustainable development.